2021
DOI: 10.3389/fonc.2021.652395
|View full text |Cite
|
Sign up to set email alerts
|

A Schistosoma japonicum MicroRNA Exerts Antitumor Effects Through Inhibition of Both Cell Migration and Angiogenesis by Targeting PGAM1

Abstract: MicroRNA (miRNA) is an important regulator for gene expression. Recent studies showed that some heterogenous miRNAs derived from both parasite and plant can regulate expression of mammalian gene in a cross-species or even a cross-kingdom manner. Here, we identified a Schistosoma japonicum miRNA (designated as sja-miR-61) that is present in the hepatocyte of mice infected with the parasite. The sja-miR-61 mimics significantly inhibited the migration of both mouse and human hepatoma cells in vitro. In a xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, a study has shown that PGAM1 interacts with ACTA2 (unrelated to its metabolic activity) to promote actin filaments assembly, cancer cell migration, and cell motility [ 39 ]. Previous studies have shown that PGAM1 promotes cancer progression by inducing angiogenesis [ 40 , 41 ]. Therefore, our results revealed an in-depth and comprehensive mode of action of PGAM1 in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study has shown that PGAM1 interacts with ACTA2 (unrelated to its metabolic activity) to promote actin filaments assembly, cancer cell migration, and cell motility [ 39 ]. Previous studies have shown that PGAM1 promotes cancer progression by inducing angiogenesis [ 40 , 41 ]. Therefore, our results revealed an in-depth and comprehensive mode of action of PGAM1 in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the parasitic miRNAs sja-miR-7-5p, sja-miR-61, and sja-miR-3096 have significant negative effects on the growth of hepatoma cell in vitro and in vivo , but no effect in normal non-cancerous cells ( Hu et al, 2019 ; Lin et al, 2019 ; Hu et al, 2021 ). Although the current study does not confirm the involvement of SjEVs during liver cancer, in-depth studies of cross-species miRNA regulation may help to discover new strategies for the prevention and treatment of parasitic diseases, including schistosomiasis.…”
Section: Micrornas In the Host-parasite Interactionmentioning
confidence: 99%
“…The overexpression of S. japonicum miRNAs with tumor-suppressor activity could function as potential therapy for cancer. It has been noted that Sja-mir-61 can inhibit the migration of liver tumor cells in vitro, and its molecular mechanism was found to involve the binding of Sja-mir-61 to the 3′-UTR region of oncogene phosphoglycerate mutase 1 (PGAM1), diminishing its expression [ 93 ]. Moreover, Sja-mir-61 was found to inhibit tumoral growth in a murine tumor model and showed antiangiogenic properties [ 93 ].…”
Section: Mirnas Of Schistosoma Japonicummentioning
confidence: 99%
“…It has been noted that Sja-mir-61 can inhibit the migration of liver tumor cells in vitro, and its molecular mechanism was found to involve the binding of Sja-mir-61 to the 3′-UTR region of oncogene phosphoglycerate mutase 1 (PGAM1), diminishing its expression [ 93 ]. Moreover, Sja-mir-61 was found to inhibit tumoral growth in a murine tumor model and showed antiangiogenic properties [ 93 ]. Sja-mir-7-5p is another miRNA with reported tumor-suppression activity and with a homologous miRNA in humans.…”
Section: Mirnas Of Schistosoma Japonicummentioning
confidence: 99%